1998
DOI: 10.1111/j.1528-1157.1998.tb01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Effect of Temporal Lobe Resection in Preadolescent Children with Epilepsy

Abstract: Summary:Purpose: Numerous studies have demonstrated changes in cognitive, memory, and language functioning in adults and adolescents after temporal lobectomy, yet little information is available regarding neuropsychological outcome in preadolescent children.Methods: We studied pre-and postoperative neuropsychological test results from 14 children who underwent temporal lobe resection for intractable epilepsy at age 7-12 years (mean 9.4 years).Results: Thirteen patients (93%) had no seizures or less than one se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
4
11

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 20 publications
4
58
4
11
Order By: Relevance
“…In children, the profile of memory impairment after surgery appears to be similar to that in adults (12,21,26) . Adams et al (1990) reported a decline of verbal memory after left temporal lobectomy, but no change after right lobectomy.…”
Section: Post-surgical Studiesmentioning
confidence: 75%
See 2 more Smart Citations
“…In children, the profile of memory impairment after surgery appears to be similar to that in adults (12,21,26) . Adams et al (1990) reported a decline of verbal memory after left temporal lobectomy, but no change after right lobectomy.…”
Section: Post-surgical Studiesmentioning
confidence: 75%
“…Szabo et al (1998) found a significant decline in immediate verbal memory after temporal lobectomy (seven right and seven left), especially in children (7 to 12 years) who had a high presurgical evaluation performance or underwent left rather than right ressections. Significant decline in the postsurgical scores of delayed memory was independent of presurgical performance and the side of the resection (26) . Duglos et al (1999) reported languagerelated cognitive decline after left temporal lobectomy (27) .…”
Section: Post-surgical Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…No estudo de Szabó et al (19) , com 14 pré-adolescentes com ELT (idade média de 9,4 anos), foram realizadas avaliações neuropsicológicas pré e pós-operatórias e constatou-se a estabilidade do QI e a diminuição da memória verbal após ressecção do lobo temporal na infância. A relativa estabilidade das medidas de QI em pré-adolescentes indica que a habilidade intelectual geral não é intensamente afetada pela ressecção do lobo temporal.…”
Section: • Alterações Mnésticasunclassified
“…Segundo Szabó et al (19) , poucos estudos avaliaram os efeitos da ELT e da lobectomia temporal na cognição de crianças com epilepsia. Na revisão realizada por estes autores, a maior parte das séries abordando este tópico tem resultados semelhantes aos dos estudos com adultos em conseqüência da população estudada, predominantemente composta por adolescentes, limitando as conclusões sobre as disfunções mnésticas em crianças pós-cirurgia do lobo temporal.…”
Section: • Alterações Mnésticasunclassified